Penile Livedoid Vasculopathy: First Reported Case - Ahmad Hallak; William Bennett; Mohammed Adib Tanbir; Supriya R. Donthamsetty; Bethaney Vincent (Case Reports in Vascular Medicine)
Livedoid vasculopathy is a thromboocclusive cutaneous vasculopathy manifested by livedoid changes, atrophie blanche, and ulceration. The pathogenesis is speculated to involve increasing coagulation or impaired thrombolysis leading to the occlusion of dermal blood vessels with fibrin thrombi. Livedoid vasculopathy is known to primarily affect the lower extremities. We report the first case of livedoid vasculopathy affecting the penis. A 60-year-old male was evaluated for a split urine stream with associated irritation and peeling of the skin of the glans penis. His penile ulcer continued to enlarge despite steroids and antibiotics. Due to diagnostic uncertainty, a biopsy was performed which revealed hyaline thrombi within the lumens of small vessels within the upper to mid dermis, fibrinoid material in the walls of these blood vessels and within the perivascular stroma with overlying and adjacent epidermal spongiosis, and mild perivascular lymphocytic infiltrate with a few scattered neutrophils most consistent with livedoid vasculitis. He was started on aspirin and pentoxifylline with limited improvement and was later started on apixaban with near-complete resolution in 6 months. Penile livedoid vasculopathy has not been previously reported in the English literature. Early diagnosis and treatment are imperative to limit morbidity.